An Ethnopedagogical Approach: The Design of AR-Based Mobile Learning of Molecular Geometry in Chemistry - Wijayanti, Sukma Wahyu; Sausan, Inas; Aditya Prasetyo, Mario (Jurnal Pendidikan Terbuka Dan Jarak Jauh, 2024)
Learning media plays an important role in supporting the learning process of chemistry, especially in the topic of molecular geometry, to enable the delivery of material more concretely and to facilitate understanding of concepts by students. To address this, there is a necessity to develop a mobile learning application based on augmented reality specifically for molecular geometry material. The process of making this application refers to the Borg & Gall (2003) development model. This model consists of 10 phases, summarized into three main parts: design, development, and evaluation. This research specifically focuses on the initial stage, namely the design stage. The research method used is research and development (R&D). This implementation plan consists of two stages: data collection through needs analysis by distributing questionnaires to students and needs analysis from a professional perspective through interviews and literature research. The result of this research is an application design with content and functionality suitable for developing augmented reality-based mobile learning materials on molecular geometry in chemistry education.